What Does It Cost to Develop a Replacement Heifer? - Matt Hersom; Todd Thrift; Joel Yelich (EDIS)
AN238, a 3-page fact sheet by Matt Hersom, Todd Thrift, and Joel Yelich, highlights the important considerations, requirements, and inputs for developing a replacement heifer. Published by the UF Department of Animal Sciences, April 2010.